Perbandingan Muatan Pendidikan Karakter dalam Kurikulum Nasional Indonesia dan Pendidikan Moral Jepang - Nur Alya Zulaiqah; Rendy Handani; Washilah Washilah; Ika Kurnia Sofiani (Reflection : Islamic Education Journal, 2026)
This study aims to analyze and compare character education in the Indonesian national curriculum with moral education in Japan. The study is motivated by the growing importance of character development in addressing global challenges and overcoming the issue of moral degradation among students. A qualitative approach with a comparative study method was employed. Data were collected through literature reviews and documentation of curriculum documents, books, and scientific journals. The data were analyzed using descriptive-comparative techniques focusing on values, educational approaches, implementation methods, evaluation systems, and cultural influences within both countries. The findings reveal that character education in Indonesia is implemented integratively across learning activities and contains diverse moral values. However, challenges remain in ensuring consistent implementation and effective value habituation. In contrast, moral education in Japan is more structured and systematic, emphasizing habit formation and the practical application of moral values in everyday life. This approach contributes to greater effectiveness in shaping student behavior. Furthermore, Japan’s success is supported by strong alignment between school practices and community cultural values. The study concludes that the effectiveness of character education depends not only on curriculum content but also on implementation strategies, evaluation mechanisms, and socio-cultural support. Therefore, Indonesia should strengthen character education through consistent habituation practices, reinforcement of school culture, and sustainable value implementation while maintaining respect for societal diversity.